Cardiovascular Imaging in Mice. Issue 1 (1st March 2016) - Phoon, Colin K.L.; Turnbull, Daniel H.
Abstract: The mouse is the mammalian model of choice for investigating cardiovascular biology, given our ability to manipulate it by genetic, pharmacologic, mechanical, and environmental means. Imaging is an important approach to phenotyping both function and structure of cardiac and vascular components. This review details commonly used imaging approaches, with a focus on echocardiography and magnetic resonance imaging and brief overviews of other imaging modalities. We also briefly outline emerging imaging approaches but caution that reliability and validity data may be lacking. © 2016 by John Wiley & Sons, Inc.